Carotid Intima-Media Thickness in Healthy Children and Adolescents: Normative Data and Systematic Literature Review - Drole Torkar, Ana; Plesnik, Emil; Groselj, Urh; Battelino, Tadej; Kotnik, Primoz (Frontiers in Cardiovascular Medicine, 2020)
Objectives. Early identification of children at risk of atherosclerosis is of paramount importance for implementing primary preventive measures addressing vascular health. Carotid intima-media thickness (cIMT) is a non-invasive biomarker of atherosclerosis. Semiautomatic radiofrequency-based software-guided technique Quality Intima-Media Thickness (RF-QIMT) was used to determine cIMT normative values in a healthy cohort of Caucasian children age 6 to 18 years. Study design. In a cross-sectional study data on age, chronic illness, medication use, and pubertal status was acquired by a questioner. Anthropometric and blood pressure measurements were performed by standardized methods and trained medical personnel. cIMT of the right common carotid artery far wall (1 centimeter proximal to bifurcation) was determined using a multifrequency (3-13 MHz) electronic linear array transducer SL1543, a portable ultrasound device (MyLab Gamma Esaote, Genoa, Italy) and RF-QIMT software. A systematic review of the published normal cIMT in children was done using PRISMA methodology and identified normative values were compared to those obtained in the presented study. Results. 1137 non-obese normotensive children (males: n=512; mean age 12.04 ± 3.52 years, females: n=625, mean age 12.98 ± 3.83 years) were included. Gender, age, and height specific mean cIMT percentile tables, percentile charts, and LMS tables for the RF-QIMT method were provided. They are comparable to the previously published data on mean cIMT gained by other validated ultrasound imaging techniques. cIMT increased with age, height, hip circumference, and BMI and was higher in males. Conclusions. Gender, age, and height specific normative cIMT values, using the semiautomatic software-guided RF-QIMT technique, in children aged 6 to 18 years were developed and validated in respect to the previously published pediatric normative cIMT data. It is suggested that the investigated method could be used for the estimation of atherosclerotic risk in children, especially in epidemiological studies.